If you build it, will they come? Assessing coaches' perceptions of a sport psychology website. Issue 3 (June 2022) - Farhat, Jade; Deck, Sarah; Mitchell, Marc; Hall, Craig; Law, Barbi; Gregg, Melanie; Pope, J. Paige; Nelson Ferguson, Kendra
Sport psychology has become widely applied in coaching practices to assist in athletic success. Despite the increased use, there is a lack of evidence-based sport psychology information available to coaches in the form of informal sources. The aim of this study was to conduct a pilot test to explore coaches' perceptions and use of an evidence-based sport psychology website. Eight coaches participated in semi-structured interviews. Based on engagement, five of the coaches' data was analyzed using thematic analysis on their experiences and revealed two main themes, website use and website enhancements. The remaining three coaches' data was analyzed for their reasons for having limited engagement with the website and used to help identify ways it could be enhanced. In general, coaches perceived the website to be a reliable source that offered practical information (e.g. worksheets) that could be used directly with athletes, and was perceived as easy to navigate and to access information. There were, importantly, various improvements suggested for the website including delivery modality and guides for navigating the order for reading the information. This study offers evidence on the value of online resources in providing coaches with informal and evidence-based sport psychology learning opportunities, and also addresses a number of barriers to engagement as insight for website developers.